IMPLEMENTASI KEBIJAKAN LAYANAN INFORMASI PUBLIK - Hendrizal ' (JIANA ( Jurnal Ilmu Administrasi Negara ), 2016)
Policy Implementation Public Information Services. This study aims to determine the implementation of the policy of public information services in Siak. This type of research is qualitative research. While the research informants include environment officials of Department of Transportation and Communication Equipment Siak, NGOs, students and people who need the information. Data collection technique were interview, observation and documentation. Data were analyzed using qualitative descriptive manner, which explains the argument any information and data obtained from the research informants. The results showed that the implementation of the policy of public information service has not done well, mainly due to the communication of information policy is not properly socialized. Constraints faced by Siak district government in realizing public disclosure caused by factors relating to human resources, financial, and facilities management.